Natural fish swim bladder-derived MPN-nanofibrous biomimetic system exhibit ECM-responsive signal regulation and promote robust tendon–bone healing - Lei Shi; Peng Zhou; Cong Ye; Jie Sun; Hongdong Ma; Ran Tao; Peng Zhang; Fei Han (Journal of Nanobiotechnology)
Abstract Enhanced tendon‒bone healing is of critically importance for achieving optimal postoperative recovery following a rotator cuff tendon tear (rotator cuff tears, RCTs). Although RCTs patch-augmented scaffolds demonstrate clinical potential, there is a paucity of reports on biodegradable scaffolds that effectively integrate high strength and bioactivity. Inspired by the composition and aligned nanofibrous structure of the natural fish bladder matrix (fish swim bladder, FSB), we employed a gallium (Ga)‒tannic acid (TA) metal‒polyphenol network (MPN)-modified decellularized fish bladder matrix (GaPP@FSB) as a novel biomaterial to address this problem. Ga-TA MPN represents a “two birds with one stone” modification strategy that allows GaPP@FSB to demonstrate commendable mechanical strength alongside multiple biological activities, including antibacterial, antioxidant, anti-inflammatory and osteogenic differentiation promotion. Furthermore, GaPP@FSB regulates the focal adhesion-based mechanical signal transduction pathway in tendon stem/progenitor cells (TSPCs), thereby activating the α5β1/Akt/PI3K pathway to induce tenogenic differentiation. Additionally, this scaffold exhibits remarkable anti-inflammatory and antibacterial activities. In a rat RCTs model, GaPP@FSB promoted regeneration at the tendon‒bone interface while restoring both rotator cuff biomechanics and joint movement function. Consequently, this biomaterial derived from natural FSB has outstanding biosafety and biological activity, making it a highly promising candidate for clinical applications in both tendon repair and the restoration of the tendon‒bone interface. Graphical abstract